Democracy and Political Participation: questioning the validity of some concepts and categories to the analysis of Latin American democracies - Camila Penna (Mediações: Revista de Ciências Sociais, 2010)
The article discusses the concepts of democracy and political participation through different perspectives aimed at pointing out the limitations as well as the contributions of some of those concepts for the analysis of Latin-American democracies. In the first section the article analyses democratic transition and democratization literature pointing out the deficiencies of the concept of democracy present in this literature when it comes to the approach of historical Latin American political process and more recent phenomenon of social mobilization in various countries. The second section discusses the participatory democracy literature and contrasts it with a minimalist conception of democracy. We argue that working under this perspective might lead to incomplete and superficial analysis of the Latin American democratization process.